Stathmin is a potential therapeutic target but not a prognostic marker in melanoma: an immunohistochemical study of 323 melanocytic lesions - Dundr, Pavel; Simon, Karol; Němejcová, Kristýna; Bártů, Michaela; Tichá, Ivana; Michálková, Romana; Jakša, Radek; Věcková, Zuzana; Kodet, Ondřej (Melanoma research, 2019)
In several solid tumors, an increased stathmin expression is associated with both poor prognosis and resistance to certain chemotherapy types. However, the data regarding melanocytic lesions are very limited. The goals of our study are as follows: the assessment of stathmin expression in benign and malignant melanocytic lesions, and the significance of its expression for the differential diagnostics between benign and malignant lesions; the analysis of the prognostic significance of stathmin expression in melanoma; and the evaluation of stathmin expression in melanoma and melanoma metastases with respect to possible therapeutic targeting. Immunohistochemical analysis of stathmin expression was done in 323 melanocytic lesions, including 205 primary cutaneous melanomas, 60 melanoma metastases, and 58 melanocytic nevi. Stathmin expression was found in all analyzed groups of melanocytic lesions. Using the H-scoring system, the observed intensity of expression was as follows: melanocytic nevi: 146.1 (mean) and 150 (median); melanomas: 116.7 (mean) and 110 (median); and melanoma metastases: 136.8 (mean) and 140 (median). The stathmin expression was significantly lower in the cohort of primary melanomas when compared with metastases and nevi (P=0.001). The stathmin expression showed no prognostic significance. The high stathmin expression in melanoma suggests that stathmin might be a promising marker for therapeutic targeting in ongoing clinical trials. Compared with several other solid tumors, stathmin expression in melanoma showed no prognostic significance. The potential use of stathmin expression in differential diagnostics is limited by its common expression, and despite the statistically significant differences between nevi and melanoma, it may not be used in this setting.
Keywords: Stathmin; Skin Neoplasms; Prognosis; Melanoma; imunohistochemie; Middle Aged; Melanocytes; mužské pohlaví; melanocyty; Biomarkers, Tumor; Immunohistochemistry; ženské pohlaví; nádorové biomarkery; melanom; prognóza; Humans; nádory kůže; lidé středního věku; Female; lidé; Male; stathmin